PRESTASI MAHASISWA PEKERJA DI FAKULTAS AGAMA ISLAM UNIVERSITAS ISLAM MALANG - Mochammad Ainul Yaqin; Ilyas Thohari; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Education in high science has an important role, one of which is in the field of work. Higher education is one of the containers of several fields of education in which there is a class of a group of students. Increasingly intense competition in various aspects of life makes students required to be able to adjust to it. Not only in terms of intellectuals, but also demanded to be able to be responsible in the social field. The phenomenon of students workers in no stranger to be found in Malang Islamic Universities especially in the Faculty of Islamic Religion. Being a student worker is certainly not easy, they are required to be able to balance between time and activities in lectures and also their work, because this will impact on the learning achievements produced. In this study using a descriptive qualitative approach with the type of case study. Researchers used insteuments in the form of observation, interviews, documentation. From 15 student workers, the work fields of student workers in the Islamic Religion faculty of Malang Islamic University include 4 students as baristas, 4 students as teachers, 2 students as online shop traders, 1 student as waiters, 1 student as wedding organizer, 1 student as guard shop, 1 student as cleaning service, and also 1 student as graphic design. Face to face lecture activities of student workers who are pursuing work as teachers have better motivation to learn, because enthusiasm when students are learning in class increasing. The average value of each semester of student workers whose work in flexible and can condition between college and work activities, has a better average grade.